Understanding the associations between the number of close friends and life satisfaction: Considering age differences - Kang, Weixi (Frontiers in Psychology, 2023)
Life satisfaction refers to one's subjective evaluation of life, which is the cognitive aspect of subjective well-being. Understanding factors that contribute to life satisfaction has important implications as higher life satisfaction is closely associated with physical, psychological, and behavioral health outcomes. Close friendship serves as a valuable source of social support across life spans. Although there are some studies regarding the associations between friendship and well-being, much less is known regarding the associations between the number of close friends and life satisfaction and how this association varies with age. By analyzing data from 29785 participants with an age range from 16 to 101 years old from Understanding Society, the current study found that there is a significant interaction effect of age by the number of close friends (b=-0.003, p<0.01, 95% C.I. [-0.004, -0.001]) after controlling for demographic covariates. Simple slope regressions showed that the number of close friends positively related to life satisfaction in young people (b=0.018, p<0.001, 95% C.I. [0.012, 0.024]), less strongly associated with life satisfaction in middle-aged (b=0.008, p<0.001, 95% C.I. [0.003, 0.013]) and older adults (b=0.004, p<0.01, 95% C.I. [0.002, 0.007]).